Ambiguity of autonarration and creating an autobiography - Hucko, Olga (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The purpose of the article is to outline the problem of the narrative unintelligibility of the way of understanding the world, of building one’s own self-image, and of the consequence of that invisibility that emanates from the autobiographical vision of one’s life. Does autonarrative reflect real life shape, as Jerzy Trzebinski describes it? How can we analyze autobiographies and autobiographical statements to reach the point of authorship? – these are some questions put in the text. In my reflections I take up the subject of the cultural script and the autobiographical pacts which I deem as necessary in the autobiographical text.